Juridical Analysis of The Duties and Authority of A Notary in Legal Consequences Of Divorce Related to Making a Deed of Distribution of Property Together - Sipahutar, Theresia; Pakpahan, Elvira Fitriyani; Azharuddin, Azharuddin (IJBLE Scientific Publications Community Inc., 2025)
Relating to the role of the Notary in property matters in Divorce In the case, joint property means that the Notary has legal standing to be able to separate and provide protection for assets whichever is considered joint or deemed property as inherited assets for both parties, the Notary has a role important in determining the status and distribution of assets within divorce The legal research method used in this research is empirical juridical research and yu Legal research menthods used in This research is normative juridical and empirical juridical research is research carried out or aimed only at written regulations and conducting research related to the implementation of the law within Community through interviews with the nature of descriptive analysis research is a menthod that functions to describe or give description of the object under study. The data source used is data primary and secondary with quantitative data analysis. The results of this research are The role of a notary in the separation of joint assets due to divorce is related with the authority of a Notary in making authentic deeds relating to agreement on the separation of joint assets as a result of a divorce, the authority to make a deed This authentication is the authority of the Notary as regulated in Law No. 30 of 2004 concerning Notary Positions Implementing the Priciple of Justice In the process of separating joint assets due to divorce, it is carried out by a mechanism for sharing joint assets that focuses on equal rights Before the law, the division of assets itself is not based on contributions who is the biggest in marriage as long as it is not determined otherwise in agreement. In the event of a divorce, the assets are divided in half evenly based on applicable laws.